Prevalence and risk factors for MSDs in vegetable greenhouse farmers: a cross-sectional survey from Shandong rural area, China - Kang, Fumei; He, Zhen; Feng, Bin; Qu, Wei; Zhang, Biao; Wang, Zhongxu (La Medicina del Lavoro, 2021)
Purpose: The aim of the research is a cross sectional survey on the prevalence of symptoms related to MSDs in vegetable greenhouse farmers from Shandong rural area and on the risk factors that may influence it. Methods: This cross-sectional survey was selected 249 farmers working in vegetable greenhouse from different districts of Shandong Province, China. The Questionnaire and the Rapid Upper Limb Assessment (RULA) technique were used to identify ergonomic risks. χ2 analysis was used to find the relationship between MSDs and various factors. Also, logistic regression methodology was applied to get the most influencing factor for MSDs. Results: The prevalence of MSDs in farmers working in vegetable greenhouse is 87.5%, and the top 3 prevalent areas of MSDs in various parts of the body are: lower back (47.4%), neck (33.3%), and shoulder (31.7%). The results of Logistic regression analysis showed that age, years working in vegetable greenhouses, keeping their backs in the same position for a long time, and working hours greater than 10 hours per day were the risk factors for MSDs in the farmers. The outcome of the RULA grand score had been found to be higher than 5 in the overwhelming majority of the farmers. Conclusions: All findings infer that each task of greenhouse vegetable growing inflicts different levels of disorder in a farmers’ musculoskeletal structure. Interventions should be increased and reduce the bad ergonomic load level as soon as possible, provided to reduce the impact of such disorders.